2019
DOI: 10.31744/einstein_journal/2019ao4423
|View full text |Cite
|
Sign up to set email alerts
|

Water protection in patients with tympanostomy tubes in tympanic membrane: a randomized clinical trial

Abstract: Objective To analyze the incidence of otorrhea in the postoperative period of patients submitted to tympanotomy to place ventilation tube, and who did not protect the ear when exposed to water. Methods Open, randomized-controlled trial. Eighty patients submitted to unilateral or bilateral ear grommet tympanostomy were included and divided into two groups: Auricular Protection and Non-Protection to water during bathing and activities in water. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Miyake et al randomized 80 children with tympanostomy tubes to “protection” with ear plugs and advice not to swim versus no ear plugs or swimming restrictions. Despite a small reduction in otorrhea with ear plugs in only the first postoperative month, there were no differences between the groups during months 2 to 13 after surgery 235 …”
Section: Guideline Key Action Statementsmentioning
confidence: 70%
See 3 more Smart Citations
“…Similarly, Miyake et al randomized 80 children with tympanostomy tubes to “protection” with ear plugs and advice not to swim versus no ear plugs or swimming restrictions. Despite a small reduction in otorrhea with ear plugs in only the first postoperative month, there were no differences between the groups during months 2 to 13 after surgery 235 …”
Section: Guideline Key Action Statementsmentioning
confidence: 70%
“…Despite a small reduction in otorrhea with ear plugs in only the first postoperative month, there were no differences between the groups during months 2 to 13 after surgery. 235…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study comparing auricular protection versus no protection, patients who had protection had a reduced risk of otorrhoea in the first month, but this equalised between groups after the first post-operative month. 3 In a similarly designed study, otorrhoea was only found to be related to water exposure in 37 per cent of the water precaution group and in 36 per cent in the non-protected group; moreover, 56 per cent and 52 per cent of cases, respectively, were in the context of upper respiratory tract infections. 4 It would therefore appear that water penetration does not influence the occurrence of otorrhoea following grommet insertion.…”
Section: Discussionmentioning
confidence: 91%